THE IMPORTANCE OF PACKAGING FOR BRAND RECOGNITION (INNOVATIVE ECONOMY, 2025)
Dudar V.T., Okrepkyi R.B. THE IMPORTANCE OF PACKAGING FOR BRAND RECOGNITIONPurpose. The aim of the article is to identify and analyse key aspects that determine how packaging contributes to the formation of a unique brand image in the minds of consumers.Methodology of research. The comprehensive approach that includes quantitative and qualitative methods was used in the research process. In particular, the method of theoretical analysis combined with empirical analysis made it possible to identify the impact of packaging design on consumer perception and behaviour; induction and deduction – to interpret the conclusions based on the research results.Findings. The research confirmed the important role of packaging as a tool for forming brand awareness and influencing consumer behaviour.It was established that the design and colour design of packaging are determining factors in forming brand awareness among Ukrainian consumers. It was substantiated that the ease of use and functional properties of packaging significantly affect repeat purchases and the level of brand loyalty. It was proven that the information richness of packaging (labelling, composition, environmental friendliness) increases trust in products and creates a positive image of the manufacturer. The differences in the perception of packaging by different age categories were analysed: young people are focused mainly on visual appeal, while older consumers are focused on functionality and quality of materials.Originality. It is proven that packaging plays not only the role of a means of preserving products, but also is a key factor in forming brand recognition, which, unlike existing approaches, allows it to be integrated into a complex of strategic marketing communications. It is substantiated that the colour scheme, material and ergonomics of packaging have a direct impact on consumer behaviour, which opens up new opportunities for brand positioning in the market. The understanding of the specifics of consumer perception of packaging in Ukraine, in particular in age and social and cultural groups has been further developed. The approach to assessing the impact of packaging as a marketing tool has been improved by combining sociological, psychological and economic research methods.Practical value. The practical novelty lies in the development of recommendations for brands that seek to increase their recognition through updating or improving the visual identity of packaging. The obtained results can be used in the activities of designers, marketers and brand managers when developing product packaging.Key words: marketing, marketing product policy, packaging, brand, product, consumer behaviour, marketing pricing strategies, pricing, advertising.
Keywords: marketing; marketing product policy; packaging; brand; product; consumer behaviour; marketing pricing strategies; pricing; advertising